2019
DOI: 10.1016/j.jaut.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric antigen receptor (CAR) T cells targeting a pathogenic MHC class II:peptide complex modulate the progression of autoimmune diabetes

Abstract: A primary initiating epitope in the NOD mouse model of Type 1 Diabetes (T1D) lies between residues 9 and 23 of the insulin B chain. The B:9-23 peptide can bind to the NOD MHC class II molecule (I-A) in multiple registers, but only one, (register 3, R3), creates complexes able to stimulate the majority of pathogenic B:9-23-specific CD4 T cells. Previously we generated a monoclonal antibody (mAb287) that targets this critical I-A-B:9-23(R3) complex. When given weekly to pre-diabetic mice at either early or late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 35 publications
0
57
0
Order By: Relevance
“…In the future, it is conceivable that engineered T cells may also be used to target also infectious diseases [41] or facilitate the induction of tolerance in transplanted recipient and individual suffering of autoimmune diseases [96,349]. It was shown that the engineering of natural Treg cells or co-transduction of T cells with specific TCRs and FoxP3 can generate Treg cells that were able to suppress arthritis in different models or mitigate autoimmunity [350,351].…”
Section: Future Applications Beyond Cancermentioning
confidence: 99%
“…In the future, it is conceivable that engineered T cells may also be used to target also infectious diseases [41] or facilitate the induction of tolerance in transplanted recipient and individual suffering of autoimmune diseases [96,349]. It was shown that the engineering of natural Treg cells or co-transduction of T cells with specific TCRs and FoxP3 can generate Treg cells that were able to suppress arthritis in different models or mitigate autoimmunity [350,351].…”
Section: Future Applications Beyond Cancermentioning
confidence: 99%
“…Importantly, there was no indication of global immune suppression. The precise mode of action of mAb287 remains unclear, but the authors speculate that selective deletion of target APCs, which in addition to presenting the B:9–23 insulin epitope also present other epitopes, could lead to an overall depletion of pMHCs [81,133]. Another possible explanation for the observed effect could be induction of specific CD4 suppressor cells in line with earlier observations using pan-MHCII mAbs [134].…”
Section: Tcr-like Mabs As Therapeuticsmentioning
confidence: 54%
“…Recently, the potential of CAR T cells as a treatment strategy for autoimmunity was explored in diabetic NOD mice. Here, CAR T cells were constructed based on mAb287 and were shown to delay onset of disease, as had been observed by the parent mAb [81,133]. Notably, whereas the parent mAb relied on weekly injections, the CAR T cells were administered once and still showed efficacy [81].…”
Section: Tcr-like Mabs As Therapeuticsmentioning
confidence: 99%
“…No engineered-T cells were detected in the treated mice, showing a limited lifespan of CAR-T cells. Taken together, these CAR-modified T cells could effectively kill APCs presenting I-Ag7:B:R3 complexes, signifying that APCs expressing the pathogenic T cell epitope are associated with autoimmunity and can be prevented by genetically modified-T cells (111). Table 2 shows further comprehensive details of CAR T-based treatment in the studies mentioned above.…”
Section: Car-t Therapy In Autoimmune Diseasesmentioning
confidence: 97%